Peran Sicantik dalam Meningkatkan Kinerja Perawat di Rumah Sakit - Eka Swedarma; Dwidasmara Dwidasmara (JURNAL KEPERAWATAN RAFLESIA, 2019)
The low ability of nurses in documenting nursing care as a result of limited human resources, too much writing format, differences in perceptions between nurses and the inability of nurses to enforce nursing diagnoses accurately will have an impact on the performance and service delivery to patients. This study aimed to fine out the nurse’s performance based on the characteristics of respondents and determine the effect of the application of the Si-Cantik application program (Electronic nursing record system) on the performance of nurses at the hospital. The research method used a one group pre-post test design approach with an intervention in the installation of an electronic nursing record system that is computer-based in the treatment room. The sampling technique used Simple random sampling with sample of 35 nurses. Statistical analysis using Chi-square test and Wilcoxon signed rank test. The results showed that the majority of respondents (77.14%) found it easy to apply the program, most nurses (77.68%) had good performance and statistically the implementation of the electronic nursing record system had an effect on nurses' performance in providing nursing care in hospitals (p = 0.004). The application of electronic nursing records system can be applied by nurses as supporting nurses' performance in providing nursing care in hospitals and becoming a reference in the use of digital nursing as an effort to develop self-potential so that they can carry out nursing services professionally.